Study On Vibration Level Of Agriculture Machinery - Aziz, Mohd Luqman Hakim Md (Universiti Sains Malaysia, 2021)
Tractor drivers are exposed to a prolonged whole-body vibration (WBV) that can cause fatigue, headache, loss of balance and "shakiness" shortly after or during exposure and, in extreme cases, disorders such as work-related musculoskeletal disorders (WMSDs). Lower back pain is one of the common work-related musculoskeletal disorders (WMSDs). Whole-body vibration usually occurs when employees drive the tractor over rough and uneven surfaces as part of their job. WBV is transmitted from the seat, handle and floor of the tractor through the bodies of the employees who drive them. Therefore, an experiment was conducted to evaluate the source of the vibration on the tractor. In this experiment, we will look at the various vibrations produced by the tractor as well as other factors. The vibration produced when the tractor moves at different speeds, the condition of the track, such as off-road and on-road conditions, and the distance of the points measured relative to the ground are all factors that will be evaluated. At first, to measure the vibration on the tractor, five accelerometers were used at five different locations. The accelerometers are connected to LMS Scadas Mobile and a laptop. LMS TestXpress13 Software is used to evaluate the effect of the three factors to generate data and graphs. From the result, we can observe the vibrational level at off road condition is higher compares to on road condition when we measured them at tractor floor. The no significance difference in the frequency for all the speeds. But we can observe the measured vibration increases, as the speed of the tractor increases. In addition, the magnitude of power spectral density at handle is higher compares to floor, thigh, body and seat. The transmissibility of the floor to the body is far greater than the magnitude of the floor to the thigh. The distance of the body relative to the ground is much higher compared to distance of floor to the ground.